+0  
 
0
584
6
avatar+466 

Show that replacing k with k + 1 in 1 - 1/2k gives an expression equivalent to 1 - 1/2k + 1/2k+1

 Feb 3, 2016

Best Answer 

 #2
avatar+94558 
+15

Show that replacing k with k + 1 in 1 - 1/2^k gives an expression equivalent to 1 - 1/2^k + 1/2^(k+1)

 

 

1  -  1/ [2^(k + 1)]  =

 

1 - 1 / [2^k * 2] =

 

1 - 1/2^k (1/2)  =

 

1 + (-1/2)(1/2^k) =                     [notice that  -1/2  =  -1  + 1/2]

 

1 + [ -1 + 1/2] [ 1/2^k]  =

 

1 - 1/2^k  + (1/2)(1/2^k)  =

 

1 - 1/2^k + 1 / [ 2^k *2]  =

 

1 - 1/2^k +  1/ 2^(k + 1)

 

 

cool cool cool

 Feb 4, 2016
 #1
avatar+95360 
+10

Hi Shades :)

 

Show that replacing k with k + 1 in 1 - 1/2k gives an expression equivalent to 1 - 1/2k + 1/2k+1

 

Going back to front it is easy enough.

 

\(1-\frac{1}{2^k}+ \frac{1}{2 ^{k+1} } \\ =1-\left[\frac{1}{2^k}- \frac{1}{2 ^{k+1} } \right]\\ =1-\left[\frac{2}{2^{k+1}}- \frac{1}{2 ^{k+1} } \right]\\ =1-\left[\frac{1}{2^{k+1} } \right]\\ =1-\frac{1}{2^{k+1} } \\\)

 

Now I want to work out how to do it in the other direction ://

 Feb 4, 2016
 #2
avatar+94558 
+15
Best Answer

Show that replacing k with k + 1 in 1 - 1/2^k gives an expression equivalent to 1 - 1/2^k + 1/2^(k+1)

 

 

1  -  1/ [2^(k + 1)]  =

 

1 - 1 / [2^k * 2] =

 

1 - 1/2^k (1/2)  =

 

1 + (-1/2)(1/2^k) =                     [notice that  -1/2  =  -1  + 1/2]

 

1 + [ -1 + 1/2] [ 1/2^k]  =

 

1 - 1/2^k  + (1/2)(1/2^k)  =

 

1 - 1/2^k + 1 / [ 2^k *2]  =

 

1 - 1/2^k +  1/ 2^(k + 1)

 

 

cool cool cool

CPhill Feb 4, 2016
 #3
avatar+95360 
+10

Show that replacing k with k + 1 in 1 - 1/2k gives an expression equivalent to 1 - 1/2k + 1/2k+1

 

We can also do this with partial fractions and then it will go in the correct direction.

 

\(1-\frac{1}{2^{k+1}}\\ =1+\;\;\frac{-1}{2*2^k}\\ \mbox{There are some integers A and B such that}\\ =1+\;\;\frac{A}{2^k}+\frac{B}{2^{k+1}}\\ =1+\;\;\frac{2A}{2^{k+1}}+\frac{B}{2^{k+1}}\\ =1+\;\;\frac{2A}{2^{k+1}}+\frac{B}{2^{k+1}}\\ =1+\;\;\frac{2A+B}{2^{k+1}}\\ \qquad SO\\ \qquad 2A+B=-1\\ \qquad \mbox{One solution to this is }\;\;A=-1\;\;and\;\;B=+1\\ =1+\;\;\frac{-1}{2^k}+\frac{1}{2^{k+1}}\\ =1-\;\;\frac{1}{2^k}+\frac{1}{2^{k+1}}\\ \)

 

[Any A and B such that    2A+B= -1   will also be true ]

 Feb 4, 2016
 #4
avatar+95360 
+10

Yours is a really nice alternate solution Chris   laugh

 Feb 4, 2016
 #5
avatar+8613 
+5

The Queen as returned!! * bows  *

 Feb 4, 2016
 #6
avatar+95360 
0

Thanks Hayley,

I still do not expect to be as conscientious as before - I still have many other things cluttering up the "to do" list ://

 Feb 4, 2016

32 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.